Изучение европейского опыта развития альтернативной энергетики - Черная, Е. Б. (НТУ "ХПИ", 2004)
Main legislative acts approved by EU for support of renewable energy development are considered. By the examples of various EU countries, political, legislative, financial, fiscal (taxation), administration factors, technological development, information, education and training that are used on national, regional and local levels for support of renewable energy are considered
Keywords: Киотский протокол; возобновляемая энергетика; энергетический спектр